Factors influencing the continuance intention to use accounting information system in Jordanian SMEs from the perspectives of UTAUT: Top management support and self-efficacy as predictor factors - Abdalwali Lutfi (Economies, 2022)
The primary objective of this study is to explain the factors that influence the continuance intention of accountants to use an accounting information system (AIS) in the context of Jordanian small and medium-sized enterprises (SMEs). Accountants are the main AIS users, and their system acceptance and use are crucial to evaluating the successful implementation of the system. The study conducted a cross-sectional survey on SMEs that have fully implemented an AIS. The proposed framework of the study is based on the extended unified theory of acceptance and use of technology (UTAUT) model and top management support (TMS). The results revealed that the examined variables, namely effort expectancy, performance expectancy and facilitating conditions, have a positive effect on the continuance intention of accountants to use AIS, with TMS having a significant and negative effect on such intention to use. In addition, social influence was found to be significantly related to continuance intention, confirming the need to support technologies such as AIS among SMEs. The study findings contribute to UTAUT theory as they supported the effects of TMS on continuance intention to use and established the study framework measurement accuracy in the context of Jordanian SMEs.
Keywords: 330; AIS; continuance intention to use; self-efficacy; SMEs; top management support; unified theory of acceptance and use of technology